Rolling Stone Brasil: aspectos de interatividade - Martins, Giuliano Trevelin [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The purpose of the present dissertation is to show the interactivity connections featured in a cultural journalism magazine's website through direct observation of its presented structure. The website chosen as object of study is Rolling Stone Brasil, April 2010 being the point of reference for analysis. Methodological support for such study has been culled from theoretical works on the principles that are necessary for the development of sampling in the observed structure. For this, are employed of concepts and strategies predicated by authors in the field of communications with emphasis on digital means is aplicated. The research indicates that the tools adopted in the website's structure comprise a potential of interactivity between the parties involved in the communication chain, and that the content therein produced may be considered as direct content of a web journalism structure

Esta monografia tem por objetivo demonstrar as relações de interatividade contidas em um site de suporte a uma revista de jornalismo cultural a partir da observação direta da estrutura apresentada. O objeto de análise é o site Rolling Stone Brasil, sendo o mês de abril de 2010 utilizado como ponto referencial da análise de estrutura contida no site. Como suporte metodológico para a análise do objeto selecionado, utilizamos obras teóricas com os preceitos necessários para se apresentar a amostra do conteúdo na estrutura observada. Para isso, são utilizados conceitos e estratégias pregadas por autores da área da comunicação voltada para o meio digital. A pesquisa aponta que o site adotou em sua estrutura ferramentas que contêm potencial de interatividade entre as partes envolvidas na cadeia de comunicação, e que o conteúdo produzido pode ser considerado como conteúdo direto da estrutura de webjornalismo
Keywords: Jornalismo; Cultura; Jornalismo eletrônico; Rolling Stone Brazil; Interactivity